2017
DOI: 10.19044/esj.2017.v13n33p276
|View full text |Cite
|
Sign up to set email alerts
|

Enquête Ethnobotanique Auprès Des Tradipraticiens De Santé Des Régions De Niamey Et Tillabéri Au Niger: Données 2012-2017

Abstract: European Scientific Journal November 2017 edition Vol.13, No.33 ISSN: 1857 -7881 (Print) e - ISSN 1857-7431 277 is the Combretaceae (10.68%), followed by Fabaceae (9.67%), Caesalpiniaceae (8.49%), Mimosaceae (7.82%), and Anacardiaceae (5, 55%). Among these plants, 60 belonging to 31 families, including 6 new families, were recorded. Several pathologies were treated. The most frequent of them are digestive disorders, hemorrhoids. Conclusion: These plants will be subjected to experimental studies before the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 0 publications
2
20
0
4
Order By: Relevance
“…The predominance of men (88%) observed in our survey population could be explained by the culture in these societies, where daily physical activities are mostly dedicated to men, women being rather busy with household tasks. Similar results were reported by [17], whose work showed that, in most African societies, physical activities are generally dedicated to men. The study reported that knowledge of traditional pharmacopoeia comes from inheritance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The predominance of men (88%) observed in our survey population could be explained by the culture in these societies, where daily physical activities are mostly dedicated to men, women being rather busy with household tasks. Similar results were reported by [17], whose work showed that, in most African societies, physical activities are generally dedicated to men. The study reported that knowledge of traditional pharmacopoeia comes from inheritance.…”
Section: Discussionsupporting
confidence: 88%
“…Traditional and cultural activities are the most important, although there are some modern sports activities including football and cycling. This reflects the importance of filial transmission of traditional and cultural knowledge and practices in African society [17].…”
Section: Discussionmentioning
confidence: 89%
“…En plus, la pratique de la médecine traditionnelle serait l'apanage des hommes d'âge mûr (Aburjai et al, 2007) [15] . [16,17,18] . Certaines recettes sont monospécifiques tandis que d'autres sont préparées en association de plusieurs espèces; ce qui permettrait de créer une dynamisation des effets curatifs des divers constituants afin d'aboutir à une synergie thérapeutique (Bla et al, 2015) [19] .…”
Section: Résultats Et Discussion Données Sociodémographiquesunclassified
“…Boire le macéré à volonté deux fois par jour matin et soir. Eviter les repas salés et gras surtout les nuits, le traitement dure trois semaines.L'utilisation de ces plantes dans la prise en charge des maladies cardiovasculaires ont été signalé dans de nombreux travaux(Dongock et al, 2018;Jazy et al, 2017;Nole et al, 2016)…”
unclassified
“…Au Niger, Eyog Matig et al (2000) ont indiqué que la poudre des feuilles mélangée avec du sel, est utilisée contre la bilharziose, ses racines sont vermifuges et que plusieurs parties sont utilisées contre la syphilis, les ulcères, les enflures. L'espèce est sollicitée pour soulager des maladies comme les carie dentaires, drépanocytose, rhumatisme, hémorroïde (Jazy et al, 2017). La décoction des fruits est utilisée contre les maladies affectant l'appareil circulatoire et celle des racines contre les maladies gynéco-obstétriques (Mounkaila et al, 2017).…”
Section: Propriétés Thérapeutiquesunclassified